Investigation of Type and Frequency of Microplastics in Municipal Solid Waste Landfills Soil: A Systematic Review - Senobar Imanian; Roqiyeh Mostafaloo; Farzaneh Fanaei; Sepideh Sahragard (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Microplastics (MPs) are an emerging pollutant with a long environmental persistence. Although several studies were conducted on MPs pollution in aquatic environments, soil environments received less attention due to the intangibility of pollution and the difficulty of evaluating MPs in soil. The present systematic study aimed to investigate the contamination of MPs in municipal waste landfill soil. Methods: This systematic review was performed in accordance with the principles of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). To that end, the databases PubMed, Science Direct, Web of Science, Scopus, Google Scholar, and internal databases of Magiran and SID were searched using the terms Microplastic, Soil, landfill, and their MeSH equivalents until 2023. Finally, 15 studies were evaluated after being screened based on the entry/exit criteria and study objectives. Results: According to studies, the type and quantity of microplastics in the soil of municipal solid waste landfills are affected by various parameters. Microplastics had different concentrations and particle sizes from less than 10 μm to more than 5 mm. Polyethylene terephthalate (PET) and polyvinyl chloride (PVC) were the most extracted chemical compounds. The MPs levels fluctuated with sampling depth and rose with the age of the landfill site and plastic components. Smaller-sized microplastics were most frequent in regions where plastic debris had been subjected to severe weathering. Conclusion: The enormous production of plastic waste and its health and ecological risks as an emerging and persistent pollutant in the environment emphasizes the importance of implementing programs to minimize plastic materials use and increase recycling of its waste. On the other hand, given the importance of soil quality in the food chain and its direct impact on air and water pollution, continuous monitoring and control of soil pollution with these substances, as well as research into the sources of their entry into the environment, can help to manage this challenge.